KAJIAN SISTEM PENGENDALIAN INTERN TERHADAP SISTEM PENJUALAN PADA PT. GIA CABANG SURABAYA - JELLYNA, ARUM (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out and to get a clear description about the application of internal control over ticket sales system which is applied by PT. Garuda Indonesia Airlines (Persero), tbk Surabaya branch and to seek out whether the internal control over ticket sales system which has been applied has been quite effective for the company. A qualitative research is used in this research and the primary data and secondary date are the type of data that is used in this kind of research. The unit of study inthis research of focused on the internal control system of sales system procedures i.e. the internal control of accounting and administrative control. The data collection techniques that are used in this research are the interview and documentation. The data analysis techniques that are used in this research are as follow: making field notes which are used as sources of data, collecting data and clarifying the data that is obtained from the field, as well as making research conclusions. The result that is obtained from this research indicate that the internal control of accounting information system of airlines ticket sales which is applied by PT. Garuda Indonesia (Persero), tbk Surabaya branch has been running adequately and affectively. The system accounting information on ticket sales at PT. Garuda Indonesia Airlines (Persero), tbk Surabaya branch has a competent human resources (HR) in carrying out the functions of duties and responsibilities that he received, the separation of the functions of a more specific task at PT. Garuda Indonesia Airlines (Persero), tbk Surabaya branch and no doubling on one personâs job function, any transactions that occur in PT. Garuda Indonesia Airlines (Persero), tbk Surabaya branch are recorded in the accounting record through certain record keeping procedures and obtain authorization from the appropriate authorities, any documents and form of transactions are numbered print series, PT. Garuda Indonesia Airlines (Persero), tbk Surabaya branch applies examination toward system and procedures through the companyâs internal audit.Keywords: evaluation, internal control, accounting information system, sales system, and effectiveness